Adaptive immunity in atherogenesis: new insights and therapeutic approaches - Lichtman, Andrew H. (American Society for Clinical Investigation, 2013)
Many remarkable advances have improved our understanding of the cellular and molecular events in the pathogenesis of atherosclerosis. Chief among these is the accumulating knowledge of how the immune system contributes to all phases of atherogenesis, including well-known inflammatory reactions consequent to intimal trapping and oxidation of LDL. Advances in our understanding of the innate and adaptive responses to these events have helped to clarify the role of inflammation in atherogenesis and suggested new diagnostic modalities and novel therapeutic targets. Here we focus on recent advances in understanding how adaptive immunity affects atherogenesis.